Evolutionary game analysis of community elderly care service regulation in the context of “Internet +” - Wang, Qiangxiang; Liu, June; Zheng, Yue (Frontiers in Public Health, 2022)
As an upgraded form of the elderly care service industry, "Internet + Community Elderly Care" integrates information technology, artificial intelligence, Internet thinking and the construction of community elderly care service mechanism. The research of "Internet + Community Elderly Care" becomes a focus. The omni-feedback mechanism that includes online-offline evaluation, complaint and return visit for elderly people is firstly introduced in this paper. The four-party evolutionary game model of elderly service regulation is then presented which consists of the governments, providers, platforms and the elderly people. Using by Lyapunov stability theory, the stability of each player’s strategy selection is analyzed. Furthermore, the sensitivity analysis of the key parameters is discussed in detail using system dynamics. Finally, the results show that the online evaluation has a more positive effect on the regulator system compared to the offline evaluation. The speculative behavior of providers and platforms can be effectively restrained by the omni-feedback mechanism of elderly people. Whether it is the governments' penalties to the providers or the subsidies to the platforms have thresholds, which should be reasonably designed with reference to relevant factors. These penalties or subsidies should also be dynamically adjusted to achieve efficient guidance for providers and platforms.